After 1851: The material and visual cultures of the Crystal Palace at Sydenham - Nichols, Kate; Turner, Sarah Victoria (Manchester University Press, 2017)
Echoing Joseph Paxton's question at the close of the Great Exhibition, 'What is to become of the Crystal Palace?', this interdisciplinary essay collection argues that there is considerable potential in studying this unique architectural and art-historical document after 1851, when it was rebuilt in the South London suburb of Sydenham. It brings together research on objects, materials and subjects as diverse as those represented under the glass roof of the Sydenham Palace itself; from the Venus de Milo to Sheffield steel, souvenir 'peep eggs' to war memorials, portrait busts to imperial pageants, tropical plants to cartoons made by artists on the spot, copies of paintings from ancient caves in India to 1950s film. Essays do not simply catalogue and collect this eclectic congregation, but provide new ways for assessing the significance of the Sydenham Crystal Palace for both nineteenth- and twentieth-century studies. The volume will be of particular interest to researchers and students of British cultural history, museum studies, and art history.